Characterisation and detection of spoilage mould responsible for black spot in dry-cured fermented sausages. (February 2015) - Lozano-Ojalvo, Daniel; Rodríguez, Alicia; Cordero, Mirian; Bernáldez, Victoria; Reyes-Prieto, Mariana; Córdoba, Juan J.
Abstract: Moulds responsible for black spot spoilage of dry-cured fermented sausages were characterised. For this purpose, samples were taken from those dry-cured fermented sausages which showed black spot alteration. Most of the mould strains were first tentatively identified as Penicillium spp. due to their morphological characteristics in different culture conditions, with one strain as Cladosporium sp. The Cladosporium strain was the only one which provoked blackening in culture media. This strain was further characterised by sequencing of ITS1-5.8S-ITS2 rRNA and β-tubulin genes. This mould strain was able to reproduce black spot formation in dry-cured fermented sausage 'salchichón' throughout the ripening process. In addition, a specific and sensitive real-time PCR method was also developed to detect Cladosporium oxysporum responsible for the black spot formation in sausages. This method could be of great interest for the meat industry to detect samples contaminated with this mould before spoilage of product avoiding economic losses for this sector. Highlights: Moulds responsible for black spots in cured sausages were characterised. Cladosporium oxysporum was identified as responsible for black spots spoilage. C. oxysporum reproduced black spots in 'salchichón' during ripening. A qPCR was developed for sensitive detection of C. oxysporum in sausages.